FACTUAL AND EXISTENTIAL PRESUPPOSITIONS IN INTERACTION AMONG LECTURERS AND STUDENTS OF INDONESIAN LANGUAGE EDUCATION DEPARTMENT AT UNIVERSITAS SEBELAS MARET - Ria Dwi Puspita Sari; Sarwiji Suwandi; St. Y Slamet (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2017)
The same presupposition in the interaction among lecturers and students become important in order to achieve the goals and create a conducive learning environment. This study aims to describe and explain factual and existential presuppositions in the interaction among lecturers and students of Indonesian Language Education, Sebelas Maret University. This research is a qualitative research by using pragmatic approach. Sources of data are in the form of speech events in the classroom, as well as informants ie lecturers and sixth-semester students. Data collection techniques are observations, interviews, listening without getting involved in the conversation, record and note. Validation of data use triangulation of data sources, methods and theories. The data analysis used extralingual equivalent technique with an advanced connecting and comparing technique. The results of this study indicate that the factual presuppositions are manifested in several contexts, they are (1) the lecturer apologies for coming late; (2) the lecturer give assessment; (3) the lecturer answer student's questions; (4) the lecturer explain the course material; (5) students answer questions; (6) students apologize for mistyped in lesson plan; (7) students describe material during microteaching practice. Existential awareness can be manifested in (1) the lecturer commented on the students' appearances microteaching practices; (2) the lecturer explained the material; (3) the lecturer suggest learning references; (4) the lecturer provide an example.Keywords: factual presupposition, existential presupposition, classroom interaction, lecturePRAANGGAPAN FAKTUAL DAN EKSISTENSIAL DALAM INTERAKSI DOSEN DAN MAHASISWA PENDIDIKAN BAHASA INDONESIA UNIVERSITAS SEBELAS MARETAbstrakPraanggapan yang sama dalam interaksi antara dosen dan mahasiswa menjadi hal penting agar tercapai tujuan dan terwujud suasana pembelajaran yang kondusif. Penelitian ini bertujuan mendeskripsikan dan menjelaskan praanggapan faktual dan eksistensial dalam interaksi antara dosen dan mahasiswa Pendidikan Bahasa Indonesia (PBI) Universitas Sebelas Maret (UNS). Penelitian ini adalah kualitatif dengan pendekatan pragmatik. Sumber data berupa peristiwa tutur dalam pembelajaran di kelas, serta informan yakni dosen dan mahasiswa PBI UNS. Teknik pengumpulan data adalah observasi, wawancara, simak bebas libat cakap, rekam dan catat. Validasi data menggunakan trianggulasi sumber data, metode dan teori. Analisis data menggunakan teknik padan ekstralingual dengan teknik lanjutan Hubung Banding Menyamakan (HBS). Hasil Penelitian ini menunjukkan bahwa praanggapan faktual berwujud dalam beberapa konteks, yakni (1) dosen meminta maaf karena datang terlambat; (2) dosen memberikan nilai untuk jawaban mahasiswa; (3) dosen menjawab pertanyaan mahasiswa; (4) dosen menjelaskan materi perkuliahan; (5) mahasiswa menjawab pertanyaan dari dosen; (6)  mahasiswa meminta maaf karena kesalahan di RPP; (7) mahasiswa menjelaskan materi saat praktik microteaching. Praanggapan eksistensial dapat berwujud dalam (1) dosen mengomentari penampilan mahasiswa ketika praktik microteaching: (2) dosen menjelaskan materi pada mahasiswa; (3) dosen menyarankan referensi belajar; (4) dosen memberikan contoh.Kata Kunci: praanggapan faktual, praanggapan eksistensial, interaksi kelas, perkuliahan